Impact of achieved blood pressure on renal function decline and first stroke in hypertensive patients with chronic kidney disease. (19th September 2017) - Li, Youbao; Liang, Min; Jiang, Chongfei; Wang, Guobao; Li, Jianping; Zhang, Yan; Fan, Fangfang; Sun, Ningling; Cui, Yiming; He, Mingli; Tang, Genfu; Yin, Delu; et al.
Abstract: Background: The effect of achieved blood pressure (BP) on first stroke and renal function decline among hypertensive patients with mild to moderate chronic kidney disease (CKD) is still uncertain. Methods: In total, 3230 hypertensive patients with estimated glomerular filtration rate 30–60 mL/min/1.73 m 2 and/or proteinuria were included in the present analyses. Eligible participants were randomly assigned to a daily treatment of a combined enalapril 10 mg and folic acid 0.8 mg tablet or an enalapril 10 mg tablet alone. Participants were followed up every 3 months. The study outcomes included first stroke and the progression of CKD. Results: The median antihypertensive treatment duration was 4.7 years. Compared with participants with a time-averaged on-treatment systolic blood pressure (SBP) of 135 to ≤140 mmHg, the incidence of total first stroke [1.7% versus 3.3%; hazard ratio (HR), 0.51; 95% confidence interval (CI): 0.26–0.99] and ischemic stroke (1.3% versus 2.8%; HR, 0.46; 95% CI: 0.22–0.98) decreased significantly in those with a time-averaged SBP of ≤135 mmHg. Furthermore, a time-averaged diastolic blood pressure (DBP) of ≤80 mmHg, compared with a time-averaged DBP level of 80 to ≤90 mmHg, was significantly related to a decreased risk of hemorrhagic stroke (0.2% versus 0.9%; HR, 0.18; 95% CI: 0.04–0.80). However, compared with participants with a time-averaged SBP of 135 to ≤140 mmHg, a lower but non-significant trend of CKD progression was found in those with a time-averaged SBP of ≤130 mmHg. Conclusions: A BP treatment level of ≤135/80 mmHg, compared with a BP treatment level of 135–140/80–90 mmHg, could lead to a decreased risk of first stroke in hypertensive patients with mild-to-moderate CKD.